Association of TNF and TLR2 genes with blood parameter levels in Mexican patients with schizophrenia - Héctor Cabello-Rangel; Carlo Esteban Sotelo-Ramírez; Joanna Jiménez-Pavon; Marco Antonio Sanabrais-Jiménez; Pamela Morales-Cedillo; Beatriz Camarena (BMC Psychiatry)
Abstract Background Clinical and genetic studies have suggested that immune dysregulation and neuroinflammation are involved in the pathogenesis of schizophrenia. Peripheral laboratory markers are accessible indicators linked to systemic inflammation and immune function. Genetic studies have demonstrated that blood parameters are highly heritable. Therefore, the aim of this study was to analyze the association between blood parameters and IL10, TNF, TLR2, and TLR6 gene polymorphisms in Mexican patients with schizophrenia. Methods We included 236 Mexican patients with schizophrenia. Peripheral blood samples were obtained in the early morning, prior the breakfast, from each participant. Complete blood count was analyzed. Genomic DNA was extracted, and genotyping was performed using TaqMan Discrimination assay of IL10 (rs1554286), TNF (rs1800629), TLR2 (rs7656411), and TLR6 (rs5743827). Association analyses between blood parameters and genotypes of the four genetic variants were performed using chi-square tests and ANOVA with Tukey’s post-hoc multiple comparisons. Results We observed higher monocyte levels (F = 5.57; p = 0.004) and monocyte-lymphocyte ratio (F = 5.49; p = 0.004) in patients carrying the GG genotype of rs7656411/TLR2 compared with TT or TG genotype carriers. Additionally, we observed a high frequency of the G allele of rs1800629/TNF, showing a low platelet count compared with carriers of the A allele (χ2 = 8.6, p = 0.003; OR = 3.82; CI, 1.46–9.96). Furthermore, we were unable to detect any gene-gene interaction in the analysis of MPV and platelet count after 1000-fold permutation testing. Conclusions Our findings indicate that blood parameter levels may be affected by genetic variants of TNF and TLR2 genes, indicating a potential role for innate immune response activation in schizophrenia in the Mexican population. Further studies with larger cohorts and comprehensive genetic analyses are essential to validate these findings and clarify the role of innate immune genes in schizophrenia.